2013
DOI: 10.2478/jas-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumer behavior relating to the purchase of honey part 2. Product quality and packaging

Abstract: A b s t r a c t Research surveys were conducted from August through December 2011 and March through July 2012, in the regions of Lower Silesia, Opole, Silesia, and Wielkopolska, Poland. Respondents were chosen randomly and a sample of 540 respondents were surveyed. The first aim of this study was to investigate the quality and aesthetic factors expected of honey and its packaging in order to establish their influence on decisions related to the purchase of honey. The second aim was to determine the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 7 publications
(9 reference statements)
2
15
1
2
Order By: Relevance
“…The result shows that consumers' sensory preferences by age, gender, and education are not identical for all regional products and that, therefore, studies should analyze sensory preferences for different food products and not generalized consumer preferences based on just one food product. The statistically significant difference between consumers with different age, gender, education, and location in the evaluation of the analyzed honey and not in the analyzed cheese and ham may be explained by the specificity of honey because the liking and choice of honey is affected by other factors like families' personal preference for certain species (Grunert, , ; Roman, Popiela‐Pleban, Kozak, & Roman, ; van Trijp, Hoyer, & Inman, ; Velčovská, ).…”
Section: Resultsmentioning
confidence: 99%
“…The result shows that consumers' sensory preferences by age, gender, and education are not identical for all regional products and that, therefore, studies should analyze sensory preferences for different food products and not generalized consumer preferences based on just one food product. The statistically significant difference between consumers with different age, gender, education, and location in the evaluation of the analyzed honey and not in the analyzed cheese and ham may be explained by the specificity of honey because the liking and choice of honey is affected by other factors like families' personal preference for certain species (Grunert, , ; Roman, Popiela‐Pleban, Kozak, & Roman, ; van Trijp, Hoyer, & Inman, ; Velčovská, ).…”
Section: Resultsmentioning
confidence: 99%
“…Batt and Liu (2012) found that in purchasing honey from a retail store (exploratory factor analysis revealed), there were three principal constructs most influential in the purchase decision: brand reputation, origin and value for the money. A study conducted by Roman, Popiela-Pleban, Kozak, and Roman (2013) showed that most consumers said they only purchase honey with domestic origin, although almost half of them said they had not checked the provenance on the label. Likewise, Pocol and Bolboac a (2013) found that respondents preferred to buy honey from a local Romanian producer and had more knowledge in domestic rather than imported honey.…”
Section: Introductionmentioning
confidence: 99%
“…According to Belay, Solomon, Bultossa, Adgaba, and Melaku (2015), many consumers still think that if honey has crystallized it has gone bad or has been adulterated with sugar, but granulation is one of the characteristics for honey. In fact, the ongoing process of crystallization applies to all honeys (Roman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…honey has crystallized it has gone bad or has been adulterated with sugar, but granulation is 103 one of the characteristics for honey. In fact, the ongoing process of crystallization applies to 104 all honeys (Roman et al, 2013). 105…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%